Spatial heterogeneity of haemoglobin concentration in preschool-age children in sub-Saharan Africa - Ricardo J Soares Magalhães; Archie CA Clements (The World Health Organization, 2011)
OBJECTIVE: To determine whether blood haemoglobin concentration in preschool-age children (< 5 years of age) is geographically heterogeneous in sub-Saharan Africa and describe its association with environmental variables that drive anaemia of different etiologies. METHODS: Data were obtained on 24 277 preschool-age children in western Africa (2862 cluster sites) and 25 343 in eastern Africa (2999 cluster sites) from the 2001-2007 Demographic and Health Surveys (DHS) for sub-Saharan Africa. Cluster sites were linked to environmental information on distance to perennial water body, elevation, land surface temperature and normalized difference vegetation index (NDVI; a proxy for rainfall) in a geographical information system. Statistical associations with environmental variables were determined using multivariate regression models, and the spatial dependence of haemoglobin concentration unexplained by these factors was quantified using semivariograms. FINDINGS: In eastern Africa, the lowest haemoglobin concentrations (< 70 g/l) occurred in small clusters throughout the region; in western Africa, they occurred in a large cluster straddling the border between Burkina Faso and Mali. Our results show significant continent-wide associations between haemoglobin concentration and environmental variables, particularly in western Africa for land surface temperature and NDVI, and in eastern Africa for elevation. Residual spatial dependence was significant, and the magnitude was greater in western than in eastern Africa. CONCLUSION: The distribution of anaemia is driven by large-scale environmental factors, and the epidemiological drivers differ in western and eastern Africa. Strategies for anaemia control in preschool-age children in sub-Saharan Africa should be tailored to local conditions, taking into account the specific etiology and prevalence of anaemia.